ANALISIS ANTESEDEN DAN KONSEKUEN PENGEMBANGAN KARIR KARYAWAN PADA PT LOYAL INDONESIA UTAMA KABUPATEN SERANG - Patinah, Dwi; Saefullah, Encep; Ende, Ende (Yayasan Education and Social Center, 2024)
Companies must have a good career planning and career management system to create employee career development programs so as to achieve job satisfaction and employee career commitment. This study aims to identify and analyze the antecedents and consequences of employee career development at PT Loyal Indonesia Utama Serang Regency. The research method used is a survey method with a descriptive quantitative approach. The population of this study were employees of PT Loyal Indonesia Utama Serang Regency, totaling 250 employees. From this population, a sample of 71 employees was obtained using probability sampling technique. This study uses the Respondent Achievement Rate (TCR) technique to analyze the data that has been collected and is assisted by the use of SmartPls 3.2.7 software as a data analysis tool. The results of this study indicate that career planning on career development results in a t-statistics value of 3.520> 1.96 and a p-value of 0.000 <0.05 so H1 is accepted, career management on career development results in a t-statistics value of 6.072> 1.96 and a p-value of 0, 000 < 0.05 then H2 is accepted, career development on job satisfaction the results of t-statistics value 3.257> 1.96 and p-values 0.001 < 0.05 then H3 is accepted and career development on career commitment the results of t-statistics value 9.199> 1.96 and p-values 0.000 < 0.05. Based on the results of hypothesis testing, it can be concluded that career planning and career management have a significant effect on career development. Career development has a significant effect on job satisfaction and career commitment in employees of PT Loyal Indonesia Utama Serang Regency